Feedback-Driven Mechanisms Between Phosphorylated Caveolin-1 and Contractile Actin Assemblies Instruct Persistent Cell Migration - Shi, Xuemeng; Wen, Zeyu; Wang, Yajun; Liu, Yan-Jun; Shi, Kun; Jiu, Yaming (Frontiers in Cell and Developmental Biology, 2021)
The actin cytoskeleton and membrane-associated caveolae contribute to active processes such as cell morphogenesis and motility. How these two systems interact and control directional cell migration is an outstanding question but remains understudied. Here we identified a negative feedback between contractile actin assemblies and phosphorylated caveolin-1 (CAV-1) in migrating cells. Cytoplasmic CAV-1 vesicles display actin-associated motilities by sliding along actin filaments or/and coupling to do retrograde flow with actomyosin bundles. Inhibition of contractile stress fibers, but not Arp2/3-dependent branched actin filaments, diminished the phosphorylation of CAV-1 on site Tyr14, and resulted in substantially increased size and decreased motility of cytoplasmic CAV-1 vesicles. Reciprocally, both the CAV-1 phospho-deficient mutation on site Tyr14 and CAV-1 knockout resulted in dramatic AMPK phosphorylation, further causing reduced active level of RhoA-myosin II and increased active level of Rac1-PAK1-Cofilin, consequently led to disordered contractile stress fibers and prominent lamellipodia. As a result, cells displayed depolarized morphology and compromised directional migration. Collectively, we propose a model in which feedback-driven regulation between actin and CAV-1 instructs persistent cell migration.